Crosstalk Between Mammalian Antiviral Pathways - Samir F. Watson; Lisanne I. Knol; Jeroen Witteveldt; Sara Macias (Non-Coding RNA, 2019)
As part of their innate immune response against viral infections, mammals activate the expression of type I interferons to prevent viral replication and dissemination. An antiviral RNAi-based response can be also activated in mammals, suggesting that several mechanisms can co-occur in the same cell and that these pathways must interact to enable the best antiviral response. Here, we will review how the classical type I interferon response and the recently described antiviral RNAi pathways interact in mammalian cells. Specifically, we will uncover how the small RNA biogenesis pathway, composed by the nucleases Drosha and Dicer can act as direct antiviral factors, and how the type-I interferon response regulates the function of these. We will also describe how the factors involved in small RNA biogenesis and specific small RNAs impact the activation of the type I interferon response and antiviral activity. With this, we aim to expose the complex and intricate network of interactions between the different antiviral pathways in mammals.